The Nurse Perceived Adequacy of Staffing Scale for general hospital wards: A development and psychometric validation study - Carmen van der Mark; Justin Bitter; Paul H.J. Hendriks; Hester Vermeulen; Catharina J. van Oostveen (International Journal of Nursing Studies Advances, 2023)
Background: Adequate staffing is crucial for high quality patient care and nurses’ wellbeing. Nurses’ professional assessment on adequacy of staffing is the gold standard in measuring staffing adequacy. However, available measurement instruments lack reliability and validity. Objectives: To develop and psychometrically test an instrument to measure nurses’ perceived adequacy of staffing (PAS) of general hospital wards. Design: A multicenter cross-sectional psychometric instrument development and validation study using item response theory. Settings: Ten general nursing wards in three teaching hospitals in the Netherlands. Participants: A sample of 881 participants, including third and fourth year nursing students and nurse/care assistants. Methods: The 13-item self-reported questionnaire was developed based on a previous Delphi study and two focus groups. We interviewed five nurses to evaluate the content validity of the instrument. The field test for psychometric evaluation was conducted on ten general wards of three teaching hospitals in the Netherlands. Structural validity of the item bank was examined by fitting a graded response model (GRM) and inspecting GRM fit. Measurement invariance was assessed by evaluating differential item functioning (DIF) of education level and work experience. We examined convergent validity by testing the hypothesis that there was at least a moderate correlation between the PAS instrument and a single item measuring adequacy of staffing. Internal consistency and reliability across the scale were also examined. Results: A total of 881 measurements were included in the analysis. The data fitted the GRM adequately and item fit statistics were good. DIF was detected for work experience for the protocols item, but the impact on total scores was negligible. The hypothesis was confirmed and the item bank reliably measured two standard deviations around the mean. Conclusions: The Nurse Perceived Adequacy of Staffing Scale (NPASS) for nurses of general hospital wards in the Netherlands has sufficient reliability and validity and is ready for use in nurse staffing research and practice.